공공병원 간호사의 안전간호활동에 미치는 영향 요인 - 이옥길(Lee, Ok Kil); 정수용(Jeong, Suyong) (근관절건강학회지, 2021)
Purpose: In this descriptive study, we aimed to identify factors influencing safe nursing activities of nurses working at public hospitals. Methods: We collected data in March 2021 through an online survey. The subjects were 199 nurses who had worked for at least six months at public hospitals. The self-reported questionnaire consisted of items pertaining to safe nursing activities, perception of patient safety culture, and the general characteristics of the subjects. To examine the differences in the safe nursing activities and perception of patient safety culture by general characteristics, we employed a t-test and ANOVA. We conducted a multiple linear regression analysis to explore the factors affecting safe nursing activities. Results: The mean score for safe nursing activity was 4.59±0.39. Perception of patient safety culture and age group were found to be the main factors affecting the safe nursing activities of nurses working at public hospitals (F=17.24, p<.001, Adj. R2=.40). When the score for perception of patient safety culture increased by 1 point, the score for safe nursing activities increased by 0.58 points. In addition, the score for safe nursing activity in the 40s age group was 0.16 points higher than for those in the 20s age group. Conclusion: Effective management and leadership in public hospitals is needed to improve the culture of patient safety at various levels so as to ensure safe nursing activities.